Education and Training on Simple Financial Statements for Hawkers Around 4th Public Elementary School Caturtunggal - Anggraeni, Dwi; Utami, Endang Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Education and training on service aims to provide an overview of simple financial statements to partners and provide guidance on the preparation of appropriate simple profit and loss, in detecting potential profits or losses experienced. Thus, it is expected that MSMEs have strong competitiveness and are able to make the right decisions when encountering potential losses. The implementation process includes observation methods, socialization and education, training, and evaluation which was held in November. The result obtained is that both partners are able to understand about simple financial statements and their role in determining the level of sales profits. In addition, they are also able to identify elements of simple financial statements and form reports with satisfactory results.